2022
DOI: 10.1002/advs.202202306
|View full text |Cite
|
Sign up to set email alerts
|

Translational Organic Neural Interface Devices at Single Neuron Resolution

Abstract: Recording from the human brain at the spatiotemporal resolution of action potentials provides critical insight into mechanisms of higher cognitive functions and neuropsychiatric disease that is challenging to derive from animal models. Here, organic materials and conformable electronics are employed to create an integrated neural interface device compatible with minimally invasive neurosurgical procedures and geared toward chronic implantation on the surface of the human brain. Data generated with these device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This might be achievable by focusing on integrating the dendrites on a substrate, something that the authors are working on and that has already been demonstrated by other groups [13,36]. When it comes to integration and integrated circuits, it is also only natural to mention the tremendous efforts done by Khodagholy's team to move toward ever more integrated neuroelectronics [37,38].…”
Section: Response Of Conducting Polymer Dendrites To Bursts Of Voltag...mentioning
confidence: 98%
“…This might be achievable by focusing on integrating the dendrites on a substrate, something that the authors are working on and that has already been demonstrated by other groups [13,36]. When it comes to integration and integrated circuits, it is also only natural to mention the tremendous efforts done by Khodagholy's team to move toward ever more integrated neuroelectronics [37,38].…”
Section: Response Of Conducting Polymer Dendrites To Bursts Of Voltag...mentioning
confidence: 98%
“…Such ultrathin flexible devices made possible the post-fabrication transfer of the OECT onto soft biological surfaces granting to record electrophysiological signals. 57,58…”
Section: Oect Architecture and Characterizationmentioning
confidence: 99%
“…Such ultrathin flexible devices made possible the post-fabrication transfer of the OECT onto soft biological surfaces granting to record electrophysiological signals. 57,58 Like metals, metal nanoparticles, and dielectric materials, OMIECs can be processed using mass production-oriented techniques such as inkjet printing, 59,60 spray printing, or roll-to-roll fabrication. 61 Although the resolution enabled by printing techniques cannot be sub micrometers; they present an appealing alternative to the time-and cost-demanding cleanroom fabrication for applications that do not require high speeds and where cost-effectiveness is more important than performance.…”
Section: Configuration and Fabricationmentioning
confidence: 99%
“…On the other hand, miniaturization of epicorticographic electrodes results in a decreased signalto-noise-ratio (SNR) with respect to large electrodes that transduce local-field potentials rather than single neuron spiking. [17] A possible route to tackle this crucial shortcoming, targets minimization of interfacial impedance by either integrating organic (semi-)conductive coatings or by means of topographic surface engineering. [18][19][20] These strategies enabled collection of neural spiking data directly from the brain cortex, broadening the clinical applicability of μ-ECoG and potentially overcoming the drawbacks of invasive intracortical electrodes, which are the golden standard for the transduction of single neuron activity.…”
Section: Introductionmentioning
confidence: 99%